The phenomenon of repetition in Surah Al-Muddathir - a phonetic-semantic study) - حسن, کوردیا احمد; کریم, هیوا عبداهلل (Sulaimani Journal for Humanities, 2025)
The aim of this research that is titled "The Repetition Phenomenon in Surah Al-Muddathir (The one wrapping Himself UP): A Phonic Semantic Study" is showing the occurrence of repetition of phonemes, syllables and their meaning according to scientific method and its outputs. If repetition is to be regarded as the key idea in the script, then this phenomenon can deepen the idea of the script. Therefore, this research emphasizes on the phenomenon of repetition in one of the chapters of the Noble Quran that is surah Al-Muddathir (the one wrapping Himself UP) by means of two aspects: phoneme and syllable. The research also aims to show the effect of this phenomenon on the listener in a way that gives comfort and relief to the good people (Muslims) and brings fear and anxiety to the bad people according to the methods of the science of mental language.